Serum IRAP, a Novel Direct Biomarker of Prediabetes and Type 2 Diabetes? - Trocmé, Candice; Gonnet, Nicolas; Di Tommaso, Margaux; Samouda, Hanen; Cracowski, Jean-Luc; Cracowski, Claire; Lambert-Porcheron, Stéphanie; Laville, Martine; Nobécourt, Estelle; Gaddhab, Chiraz; Le Lay, Allan; Bohn, Torsten; et al. (Frontiers in Molecular Biosciences, 2021)
Insulin resistance, currently called prediabetes (PD), affects more than half of the adult population worldwide. Type 2 diabetes (T2D), which often follows in the absence of treatment, affects more than 475 million people. A preventive public health policy is urgently needed to stop this progressing epidemic. Indeed, early management of prediabetes reduces its evolution towards T2D and the appearance of comorbidities There is however currently no reliable test for the diagnosis or screening of PD and it is estimated that 20 to 60 % of diabetics are un diagnosed. We developed an ELISA for the quantitative determination of serum IRAP which associated with and translocated to the plasma membrane together with GLUT4 in response to insulin in the two major glucose storage sites. Its extracellular domain is subsequently secreted in the blood stream. In T2D, IRAP translocation is strongly decreased. Our patented sandwich ELISA is highly sensitive (≥ 10.000-fold "normal" fasting concentrations), specific, robust and very cost-effective. Dispersion of fasting plasma values in a healthy population is very low (101.4 ± 15.9 µg/ml) as compared to those of insulin (21 - 181 pmol/l) and C-peptide (0.4 – 1.7 nmol/l). Results of pilot studies indicate a correlation between IRAPs levels and insulin-sensitivity. We therefore think that plasma IRAP may be a direct marker of insulin-sensitivity and that the quantitative determination of its plasma levels should allow large-scale screening of populations at risk for PD and T2D, thereby allow the enforcement of a preventive health policy aiming at efficiently reducing this epidemic.